Mapping Journals and Researcher Contributions in the Realm of Islamic Economic Education: A Bibliometric Review - Ilhamiwati, Mega; Siminto, Siminto (Westscience Press, 2024)
This bibliometric review provides a systematic analysis of scholarly contributions in the realm of Islamic economic education, a multidisciplinary field that integrates Islamic principles with contemporary economic theory and practice. Drawing upon bibliometric techniques including citation analysis, keyword co-occurrence analysis, and visualization tools, the study identifies prominent journals, highly cited publications, thematic clusters, and emerging trends within Islamic economic education. The findings offer insights into the evolution, impact, and future directions of research in this field, highlighting its significance in promoting economic empowerment and social justice within Islamic societies. Practical implications derived from the analysis inform curriculum development, policy formulation, and strategic planning initiatives, facilitating informed decision-making for academia, policy-makers, and practitioners. Overall, this bibliometric review contributes to advancing knowledge in Islamic economics and underscores its relevance in addressing contemporary socio-economic challenges.